2022
DOI: 10.1186/s12875-022-01863-z
|View full text |Cite
|
Sign up to set email alerts
|

Health care professionals’ perspectives on the utilisation of a remote surveillance and care tool for patients with COVID-19 in general practice: a qualitative study

Abstract: Background Most COVID-19 patients with severe symptoms are treated in hospitals. General practices are responsible for assessing most ambulatory patients. However, they face several challenges managing COVID-19 patients, and those with non-COVID-19 conditions. In April of 2020, we designed a software tool for the structured surveillance of high-risk home-quarantined COVID-19 patients in general practice (CovidCare) including several telephone monitorings, in order to support general practices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…General practitioners support or lack thereof influenced the perceived stress. Incomplete knowledge on depression increased strain Burdening and relieving factors Interaction with depressed patients Collaboration with doctor Disease conception [ 53 ] Hoffmann et al 2022 12 v Qualitative, cross-sectional; semi-structured interviews To present the qualitative results from the process evaluation of an intervention for COVID-19 surveillance and care for COVID-19 patients with increased risk used by VERAHs (specially qualified MA) and general practitioners Sense of security The implementation of the intervention gave MA a sense of security and support. MA emphasized additional workload as particularly negative because the intervention added additional tasks and strain in the already tightly organized daily practice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…General practitioners support or lack thereof influenced the perceived stress. Incomplete knowledge on depression increased strain Burdening and relieving factors Interaction with depressed patients Collaboration with doctor Disease conception [ 53 ] Hoffmann et al 2022 12 v Qualitative, cross-sectional; semi-structured interviews To present the qualitative results from the process evaluation of an intervention for COVID-19 surveillance and care for COVID-19 patients with increased risk used by VERAHs (specially qualified MA) and general practitioners Sense of security The implementation of the intervention gave MA a sense of security and support. MA emphasized additional workload as particularly negative because the intervention added additional tasks and strain in the already tightly organized daily practice.…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies that examined psychosocial working conditions of MA during the COVID-19 pandemic reported an increased workload [ 51 , 53 ], with one study reporting MA being overwhelmed by the situation [ 53 ]. Studies examining the implementation of interventions reported barriers in MA taking up new tasks and/or responsibilities in the context of these interventions due to an already existing lack of time [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The German health care system is currently developing strategies to expand home-based care in order to decrease the burden placed upon the hospital sector ( 64 ). Remote home monitoring models could reassure patients during home based isolation and care ( 19 , 65 ), but more studies are needed to generate evidence for appropriate care ( 66 ) and the utility of different tools, such as pulseoxymetry ( 56 , 66 , 67 ). We showed that special attention should be placed on people living alone, with preexisting comorbidities or of old age.…”
Section: Discussionmentioning
confidence: 99%
“…During the course of the pandemic, health care systems had to prove resilience (17) finding new ways to ensure COVID-19 diagnosis and care, while adapting to hygiene, quarantine and isolation measures enforced to combat the spread of the disease. The adapted health structure included new modes of care and stakeholders: Telehealth services were rapidly expanded (18)(19)(20). In Germany, public health services (Öffentlicher Gesundheitsdienst) gained more influence and became a central player in patient management and implementing COVID-19 related policies (21) alongside general practitioners (GPs) who traditionally coordinate patient-centered prevention and care.…”
Section: Introductionmentioning
confidence: 99%